Successful tocilizumab treatment for rapidly progressive interstitial lung disease with anti-MDA5-positive juvenile dermatomyositis: a case report and literature review - Qiu, Lingzhi; Shao, Xiaoyan; Ma, Le; Fan, Zhidan; Yu, Haiguo (Frontiers in Pediatrics, 2024)
Background: Currently, there is no established integrated treatment regimen for anti-melanoma differentiation-associated gene 5 (anti-MDA5) positive juvenile dermatomyositis (JDM) complicated by rapidly progressive interstitial lung disease (RP-ILD). We present a case of refractory anti-MDA5 positive JDM with RP-ILD that was successfully treated with a combination of tocilizumab and plasma exchange, along with a review of relevant literature.Methods: A literature review was conducted to gain insights into the clinical features and treatments strategies for refractory anti-MDA5 positive JDM complicated by RP-ILD.Results: We report a case of successful management of anti-MDA5 positive JDM complicated by RP-ILD through the use of a combination of immunosuppressive agents, plasma exchange, and tocilizumab.Conclusion: Tocilizumab may serve as an effective adjunctive treatment for patients with refractory anti-MDA5 positive JDM complicated by RP-ILD who do not respond to conventional intensive immunosuppressive therapies.